A novel time-domain technique for damage detection applied to SHM using Savitzky-Golay filter - Anderson De Oliveira, M.; Filho, J. V. [UNESP]; Junior, V. L. [UNESP]; Inman, D. J. (My University, 2013)
This paper presents a novel damage detection approach for Structural Health Monitoring (SHM) sy stems, which is based on Savitzky-Golay filter and time-domain analysis. In this technique, a specific P ZT (actuator) excites the structure and three other ones are used as sensors to receive the structural responses. This method is quite similar to L amb wave based methods, but the excitation procedure and the analy sis of the respon se sig nals are different. F or the prop osed method, a wide band chi rp sig nal, with low amplitude and variable frequenc y, is used to excite the structure. The response signals are acquired in time-domain and smoothed by a Savitzky-Golay filter, and from the filtered signals the first and second derivatives are computed. CCDM (Correlation Coefficient Deviation Metric) indices are calculated from all signals (smoothed, first and second derivatives), considering the structure a healthy condition as a reference (baseline). Practical tests were carried out on an aluminum plate a nd the resul ts have de mons trat ed the e ffec t iveness of the pr oposed met hod.